The Global Ocean Biodiversity Initiative: Promoting scientific support for global ocean governance. (21st October 2019) - Johnson, David; Barrio Froján, Christopher; Bax, Nicholas; Dunstan, Piers; Woolley, Skipton; Halpin, Pat; Dunn, Daniel; Hazin, Carolina; Dias, Maria; Davies, Tammy; Jiménez, Jorge; Ross, Erick; et al.
Abstract: Addressing the challenge of protecting biodiversity in the global ocean requires a sound knowledge and understanding of the complex marine environment. Since 2008 the Global Ocean Biodiversity Initiative (GOBI) has been established as a voluntary dedicated group of marine institutions and scientists working to support conservation and protection of marine biodiversity. A focus has been work to support the Convention on Biological Diversity's Ecologically or Biologically Significant Marine Area (EBSA) process. GOBI partners have provided expert interpretation of evidence‐based information and sought to compile and collate available information. An effective and coherent global network of marine protected areas must include bioregional representative replicates of features; once described, EBSAs can help focus attention on where and what kind of protective measures may be needed. GOBI is currently undertaking a 5‐year programme of research funded by the German International Climate Initiative, working to strengthen baselines and contribute new data to the EBSA and other processes. This involves developing detailed biogeographies for the Pacific and Indian Oceans, assessing the movement of migratory species, advancing understanding of biodiversity at vents and seeps, developing a model governance system for the Costa Rica Thermal Dome, and incorporating Important Bird and Biodiversity Areas and Important Marine Mammal Areas. GOBI has taken initiatives to build on the results of the Census of Marine Life and ensure best available marine biodiversity information is considered by states and intergovernmental organizations. GOBI support for ocean governance, including data development and expert consultation, will also contribute to the United Nations Decade of Ocean Science for Sustainable Development (2021–2030). Future challenges include capacity building and new approaches to incorporate traditional knowledge.